2016
DOI: 10.4103/0366-6999.177969
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence and Mortality Survey in Wuwei, Gansu Province, Northwestern China from 2003 to 2012

Abstract: Background:Population-based cancer registry collects the data on cancer incidence and mortality deaths from covered population to describe and survey the epidemics in certain areas. The aim of this study was to estimate the cancer incidence and mortality in Wuwei, Gansu province, Northwestern China from 2003 to 2012. The goal is to better understand cancer distribution and long-term development of cancer prevention and treatment in Wuwei.Methods:Data were collected from the Wuwei Cancer Registry between 2003 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…The age-specific incidence rates in males were all lower than females for individuals 25–54 years old, while for individuals over 55 years old, the age-specific incidence rates in males were all much higher than females. The results are consistent with those in some studies [ 3 , 7 , 18 ], which showed that the cancer incidence increased gradually with age and cancer incidence was higher in males than females over 50 years old. The results could be attributed to some risk factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The age-specific incidence rates in males were all lower than females for individuals 25–54 years old, while for individuals over 55 years old, the age-specific incidence rates in males were all much higher than females. The results are consistent with those in some studies [ 3 , 7 , 18 ], which showed that the cancer incidence increased gradually with age and cancer incidence was higher in males than females over 50 years old. The results could be attributed to some risk factors.…”
Section: Discussionsupporting
confidence: 93%
“…There are some factors that are possibly contributing to the growing incidence and mortality of cancer in developing countries, which include population aging and growth, smoking, physical inactivity, unhealthy diets, environment pollution and occupation exposure [ 4 , 5 , 6 ]. In particular, the environment pollution, high density population and bad health lifestyles are still serious problems need to be solved in China, which contribute to the obvious increase in the incidence of cancer [ 7 ]. Thus, obtaining knowledge about the situation of cancer and controlling the growth in the incidence of cancer are goals that the governments around the world should achieve.…”
Section: Introductionmentioning
confidence: 99%
“…1 Gastric cancer is one of the most common types of cancer according to a ten-year tumor statistics analysis from Wuwei district, Gansu province, China. 2 Most patients with gastric cancer are diagnosed at an advanced stage due to lack of early symptoms and the limitations in screening programs. 3 However, lack of effective treatments for gastric cancer and the challenge of chemotherapy resistance are still great problems in gastric cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…According to the report of world health organization (WHO), the number of cancer-related deaths was 6 million in 2000, 7.6 million in 2005, and 7.9 million 2007, and this reveals 32% growth in the number of deaths during 2000 to 2007 (9). In 2007, 13% of the deaths were assigned to cancer and 72% occurred in developing countries (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Considering this growth in incidence rate, there will be 13 million cancer-related deaths in 2030, 9 million of which will occur in developing countries (15). Increasing in the cancer burden mainly depends on the growth of population and aging (increasing in life expectancy) (3, 4, 13-21) also, risk factors and harmful life style (10,13,14,20). Changing in fertility rate (4,20) and life expectancy are two main factors affecting population pyramid (22), which can cause problems in countries with different levels of financial supports and funds.…”
Section: Introductionmentioning
confidence: 99%